Strategi Peningkatan Kualitas Produk dan Keputusan Pembelian Pada PT. XYZ - Atikah Atikah; Sungkono Sungkono (Journal of Management and Social Sciences, 2023)
This study aims to describe how product quality can influence purchasing decisions and how the working atmosphere at PT. Chang Shin Indonesia. This study used the observation method by directly observing the situation in the field and interviewing several employees. In the world of work, there are often problems related to the products we create, as well as those involving product quality at PT. Chang Shin Indonesia, which after the end of last year was at the peak of instability in running production. PT. Chang Shin Indonesia itself is a company that produces footwear with the “Nike” brand, by producing footwear for the company PT. Chang Shin Indonesia is very focused on the quality of the products it creates. Problems found in PT. Chang Shin Indonesia, namely the reduction of a purchase decision or order from a customer, one of which causes employees to stay at home on Saturdays, which basically work normally on Saturdays as usual. Reduced orders greatly impact the company, especially on employees. One of the factors that affected the decline in orders was in terms of product quality. For example, many long threads are still attached to finished shoes and also the size label where there are many repairs, one of which is that the label does not match the tally sheet. This problem is often found in the sewing or stitching department. Based on the results of these observations, it is necessary to pay attention again regarding product quality, both by the company and its own team of employees who are required to maintain product quality, because whether or not orders enter the company depends on quality.